Neuroimaging Biomarkers of mTOR Inhibition on Vascular and Metabolic Functions in Aging Brain and Alzheimer’s Disease - Lee, Jennifer; Yanckello, Lucille M.; Ma, David; Hoffman, Jared D.; Parikh, Ishita; Thalman, Scott; Bauer, Bjoern; Hartz, Anika M. S.; Hyder, Fahmeed; Lin, Ai-Ling (Frontiers in Aging Neuroscience, 2018)
The mechanistic target of rapamycin (mTOR) is a nutrient sensor of eukaryotic cells. Inhibition of mechanistic mTOR signaling can increase life and health span in various species via interventions that include rapamycin and caloric restriction. In the central nervous system, mTOR inhibition demonstrates neuroprotective patterns in aging and Alzheimer’s disease (AD) by preserving mitochondrial function and reducing amyloid beta retention. However, the effects of mTOR inhibition for in vivo brain physiology remain largely unknown. Here we review recent findings of in vivo metabolic and vascular measures using non-invasive, multimodal neuroimaging methods in rodent models for brain aging and AD. Specifically, we focus on pharmacological treatment (e.g., rapamycin) for restoring brain functions in animals modeling human AD; nutritional interventions (e.g., caloric restriction and ketogenic diet) for enhancing brain vascular and metabolic functions in rodents at young age (5-6 months of age) and preserving those functions in aging (18-20 months of age). Various magnetic resonance (MR) methods (i.e., imaging (MRI), angiography (MRA), and spectroscopy (MRS)), confocal microscopic imaging, and positron emission tomography (PET) provided in vivo metabolic and vascular measures. We also discuss the translational potential of mTOR interventions. Since PET and various MR neuroimaging methods, as well as the different interventions (e.g., rapamycin, caloric restriction, and ketogenic diet) are also available for humans, these findings may have tremendous implications in future clinical trials of neurological disorders in aging populations.